PENGARUH PEMANASAN BAHAN BAKAR MELALUI PIPA TEMBAGA BERSIRIP RADIAL DI DALAM UPPER TANK RADIATOR DAN PENAMBAHAN ETANOL PADA BAHAN BAKAR TERHADAP KONSUMSI BAHAN BAKAR - Ivan Arianto; Danar Susilo Wijayanto; Ngatao Rohman (Nozel : Jurnal Pendididikan Teknik Mesin, 2020)
This research aims to test: (1) to know the effect of fuel heating through radial finned pipe in upper tank radiator to fuel consumption of Suzuki APV car, (2) to know the effect of ethanol addition on fuel of gas type pertalite to fuel consumption of Suzuki car APV, and (3) know the effect of fuel heating through radially finned pipes inside the upper tank radiator and the addition of ethanol to the fuel to the fuel consumption of Suzuki APV cars.This research uses experimental method with comparative descriptive data analysis. The research sample used is Suzuki APV with machine number G15A1D100006. Data obtained from the amount of fuel consumption in one minute at idle cycle with variation of percentage of mixed pertalite and ethanol 0%, 5%, 10%, 15%, 20%, 25%, and 30% using the method without heating fuel and using heating Fuel radial finned capillary pipes within the upper tank radiator. The data obtained from the research results are inserted into the table and displayed in graphical form, then analyzed.The results of this research is: (1) the use of fuel heating using radially finned pipe in the upper tank radiator increases fuel consumption in Suzuki APV engines. The highest increase in fuel consumption on fuel heating using radially finned pipes with a spacing of 10 mm fin without ethanol mixture of 81.67 ml / min. Difference of consumption is 20 ml / min or 32.4% of standard state consumption,(2) the addition of ethanol in gasoline can reduce the fuel consumption of Suzuki APV cars. The variation of ethanol addition to the most economical fuel when adding 20% ethanol content of 51.67 ml / min. Difference in consumption 10 ml / min or 16.21% of standard state consumption, (3) the addition of ethanol to fuel and heating fuel decreases fuel consumption on Suzuki APV engines. The largest decrease in consumption at 20% ethanol content and no fuel heating of 51.67 ml / min. Decrease in consumption by 10 ml / min or as much as 16.21% of fuel consumption in the standard state.